Dimensions of Cultural Values - Šalčiuvienė, Laura (Ekonomika, 2002)
Marketers have long acknowledged the importance of attitudes and attitude change in the study of marketing and market research, but the role of values has received relatively little attention. In this paper secondary data is used to present the ethnic and social cultural impact on cultural values.A three-level structure of the individual value system, which is derived from ethnic peculiarity, level of adaptability to the former or new created social and economic environment, and one’s owns decisions, is applied.The identification of Lithuanian cultural values and explanation of derived hypotheses are based on information received using O-sort scaling and survey methods.